2016
DOI: 10.1111/asj.12697
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different rearing systems on growth, small intestinal morphology and selected indices of fermentation status in broilers

Abstract: A 3×2 factorial experiment was conducted to determine the effects of rearing system and stocking density on the growth performance, intestinal morphology and fermentation status of broilers. Broilers were kept on three rearing systems: floor litter rearing (FRS), plastic net rearing (NRS) and multilayer cage rearing system (CRS), each with two stocking densities (normal and high stocking densities). Results showed that on 7 to 28 days of age, body weight gain appeared as FRS > NRS > CRS. Whereas, CRS significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 30 publications
6
29
1
Order By: Relevance
“…Growth performance is an important index used to evaluate poultry production and can be affected by different rearing systems (Liu et al., ). Consistent with the findings of previous studies (Li et al., ; Wang et al., ), we found that the different rearing systems examined in this study had a significant influence on growth performance. It was reported that Gushi female chickens raised under free‐range conditions had lower body weight and weight gain compared with birds raised under indoor conditions (Wang, Shi, Dou, & Sun, ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Growth performance is an important index used to evaluate poultry production and can be affected by different rearing systems (Liu et al., ). Consistent with the findings of previous studies (Li et al., ; Wang et al., ), we found that the different rearing systems examined in this study had a significant influence on growth performance. It was reported that Gushi female chickens raised under free‐range conditions had lower body weight and weight gain compared with birds raised under indoor conditions (Wang, Shi, Dou, & Sun, ).…”
Section: Discussionsupporting
confidence: 93%
“…The most widely and commonly used rearing systems are free‐range (FRS) and conventional cage‐rearing systems (CRS), and the chickens are raised under CRS conditions tending to show superior feed efficiency and growth performance (Wang et al., ). Similar findings had been reported for different poultry breeds, including broiler chickens (Li et al., ), laying hens (Al‐Ajeeli et al., ), and local ducks (Zhang et al., ). Moreover, compared with other rearing systems, the CRS is an effective approach for maximizing the utilization of space and stocking density, and decreasing administrative costs and exposure to contaminants.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Though CRS makes full use of the breeding house space, ducks were vulnerable as individual activities are much constrained [1]. Whereas, FRS is usually to lay a thick pad of 5-10 cm by straw, sawdust or wood shavings on a cement oor [6][7][8], which could absorb excess moisture but has defects in rearing management. Plastic oor net-rearing and wire oor net-rearing are national wide applied NRS.…”
Section: Introductionmentioning
confidence: 99%
“…Gut flora has been proven to be influenced by external factors such as cleanliness at and after birth, how the young are fed, and early birth (Gibson, Crofts, & Dantas, 2015). High stocking density may lead to an increase in pathogens that affect the digestive tract, although this is a relatively unstudied subject (Li et al, 2017;Weber et al, 2015). In this study, we explored the effects of different stocking densities on the expression of markers for oxidative stress and the presence of commensal gut bacteria.…”
Section: Introductionmentioning
confidence: 99%